A csanádi egyházmegye mint régiószervező tényező = The diocese of Csanád like region-organizing factor - Miklós, Péter (Közép-Európai Közlemények, 2018)
The Diocese of Csanád can be research like region-organizing factor. It was not only the bishop’s town, but it was also an educational, cultural, scientific, economical és governmental center. The center of the Diocese of Csanád was Csanád city (now: Cenad, Roumania) from 1030 until 1550. Csanád was destroyed by the Ottoman Turkish occupants. The Holy See of Csanád was in Temesvár (now: Timisoara, Roumania) from the first part of 1700’s. The Diocese of Csanád was decomposed by the Peace Treaty of Trianon (1920) and the center – by bishop Gyula Glattfelder – was moved to Szeged (Hungary). This study persents that Csanád, Temesvár and Szeged was regional scope ecclesiastical center over the last centuries. The Catholic Church – by the Diocese of Csanád – was society and economic power in the Hungarian Southern Great Plain. The Diocese preserved schools, academic institutions, and business associations (primarily agronomic possesions). The sources of this essay were the relevant literature and archival documents.